ACHIEVEMENT OF NATIONAL EDUCATION OBJECTIVES THROUGH THE RESEARCH OF STUDENT’S ENVIRONMENT AND EDUCATION CHARACTER - suhendar suhendar (Journal of English Language and Literature (JELL), 2017)
The objectives of this research are to find out the result of achievement of national education objectives through environmental research of students and through the characteristics of education. This study used descriptive qualitative research. In connection to which, this research constitutes one of teacher’s best endeavors to know the attainment of education objectives and to ensure that teaching and learning activity in the class runs well, hence, the quality of education for students in the society can be accordingly improved